Memetic Warfare - Khatunov, Sergei (YSU Journal of International Affairs, 2022)
Today the military should master a new approach to the conduct of hostilities based on the alternative thinking when using new elements of military-political power. It is necessary to use alternative thinking, one of which is a meme, in order to influence the ideological sphere of eventual enemies in order to gain an advantage in the ideological metaphysical battle. Memes are new tools for winning war. In this article we examine memetic warfare as an instrument used to divide the society, so we explain the root causes of the emergence and use of pathogenic memes, socalled mind viruses, which are actually difficult to eliminate. Therefore, in order to successfully fight on the battlefields of future, we must have professionals creating memes. Armenia must recognize the growing need for new fighters in ideological warfare ready to create memes with a powerful weapon effect. Competition is at all levels and people need to develop faster both mentally and physically, than their rivals, to be successful. Natural selection must take place not only in a genetic but also in a memetic environment. Now armed struggle has received new tools - memes, which become weapons with the advent of high-precision digital media technologies and declare a memetic war. Memes have radically changed our world and not to change anything in military affairs and not to work on strengthening the memetic power - this means to ignore the law of dependence of the forms and methods of the armed struggle on the forces and means of its conduct. Moreover, this may lead not to the disappearance of the law, but to the disappearance of those who ignore the law. Compliance with the laws of warfare is a key factor in achieving victory on all battlefields, present and future.